InsuTAG and Early Salutogenic Screening of Cardiometabolic Risk in Obese Adolescents - Inner Beauty Bilqis, Tiber Raniar; Widjaja, Nur Aisiyah; Devy, Shrimarti Rukmini; Indriani, Diah; Irawan, Nur Roedi; Hanindita, Meta Herdiana; Ardianah, Eva (Universitas Airlangga, 2026)
Background: Insulin resistance (IR) is considered the common underlying cause of metabolic syndrome (MetS). Predicting the incidence of MetS and IR at the individual level is essential, especially in obese adolescents who are at high risk of cardiovascular disease (CVD). InsuTAG has shown reliable results in predicting IR and MetS in healthy elderly populations. This study aimed to investigate the use of InsuTAG as an assessment tool to predict IR and MetS in obese adolescents, using the homeostasis model assessment (HOMA) to quantify insulin resistance. Methods: A cross-sectional analytic study was conducted from January to May 2020 in healthy obese adolescents aged 13-18 years-old. Blood analyses included lipid profile (LDL-c, HDL-c, total cholesterol, and triglycerides), fasting blood glucose, and fasting insulin. IR was defined as HOMA-IR > 5.22 for boys and > 3.82 for girls during the pubertal period. Results: The receiver operating characteristic (ROC) curve for InsuTAG demonstrated a greater area under the curve (AUC) for identifying IR than MetS (0.877 vs. 0.743, p = 0.000; 95% CI). The optimal InsuTAG cut-off to determine IR was > 23.48, with 78.43% sensitivity and 87.38% specificity. The cut-off to identify MetS was > 23.36, yielding 67.97% sensitivity and 72.82% specificity. Conclusion: InsuTAG is a useful tool for identifying IR and MetS. The optimal cut-off values are > 23.48 for IR and > 23.36 for MetS in obese adolescents. These findings support early prevention and health promotion efforts, ultimately strengthening self-care practices among obese adolescents.